Effects of Electrospinning Parameters on the Morphology of Electrospun Fibers - A. Ardakkyzy; N. Nuraje; Zh. Toktarbay (Eurasian Chemico-Technological Journal)
Hydrophobic electrospun membranes have a lot of applications in different fields. It is very difficult to increase the hydrophobicity of membranes for a specific application. This study investigates the effects of various electrospinning parameters on the morphology and hydrophobicity of polystyrene (PS) electrospun membranes. Polystyrene fibers were used as a reference for the study. Different parameters such as polymer concentrations, diameter of needles, and applied voltage were tested to study the influence on the hydrophobicity of electrospun fibers. Polystyrene fibers were electrospun at different concentrations from 5 to 20 wt.%, needles with a diameter from 0.5 to 3 mm were used, and voltage was applied between 8.06–16.05 kV. The surface morphology of polystyrene fibers and hydrophobicity were studied with a scanning electronic microscope and contact angle measurements. Based on the results of the study, higher polymer concentrations and voltages produce thinner fibers and more hydrophobic membranes. The results of this paper can be applied to the fabrication of different characteristic membranes for specific applications like water conservation, purification, and other fields.